The Role of Judicial Commission on Supervision of Judge’s Crime in Indonesia - Ahmad Firmanto Prasedyomukti; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This booklet is designed to examine the effectiveness of the Judicial Commission's role in the supervision of judge’s crime in Indonesia, as well as existence. Based on the discussion, we can conclude: 1) The role of the Judicial Commission in the framework of the supervision of judge’s crime has not been effective, due to the legal existence of the Judicial Commission recognized but on a practical level does not have the authority to impose administrative punishment on their own, the Judicial Commission had no authority investigations against the judge found to have violated the rules of the criminal. 2) Need for reconstruction of the existence of the Judicial Commission under the supervision of judge’s crime offense, so there is a balance between the authority of the Judicial Commission and the follow-up comprehensively.Keywords: Judicial Commission; Supervision; Judge.